(3GdOQ GdMdhc GdeTQb HOQI GdSdhc ajef Mhi Gdedc ef Gdedhcs - (3CMeO Hf eMeO Hf eMeO Hf CHj GdYGajI GdecfGSj GdRfGJj, CHh GdYHGS Hf GdbGVj,J (B1025 (3g` s
(3ChdgG (B:s
(3deG CQGO Gddg JWgjQ GdhQi hCf jHOO GdLOGd hGdeQG s
(3BNQgG (B:s
(3gPG eG bUOJ ef TQM OQI GdSdhc hcGf GdaQGZ ef LeYg HeQGcT YTjI jhe GdLeYI (B19 (3QLH GdaQO YGe (B1000 (3ef GdgLQI s
(3Vef eLehY , JQJjHgG (B: (3ef U C (B14 - (3U H (B21s
(3hgh TQM GdefXheI GdoeSeGI HOQI GdSdhc ajef Mhi Gdedc ef Gdedhc LYdg cGdPjd dQbe GdMdd ddSGf GdOjf Hf GdNWjH GdSdeGfjs
(3hGdehLhO efg GdbSe GdNGU HGdOhdI GdSYOjI abWs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJGQjNs